Successful management of congenital bronchial web in an adolescent using bronchoscopic ablation: A case report and review of literature - Sara G. Hamad (17337700) (2023)
Airway webs are abnormal fibrous membranes in the airway lumen that rarely occur but can lead to serious or even life-threatening symptoms because of critical airway obstruction. Airway webs can be acquired or congenital. Acquired webs are likely to be secondary to trauma, infections, or neoplasm. Congenital laryngeal, subglottic and tracheal webs present early in infancy or childhood and are more common than congenital bronchial webs. To our knowledge, there are a few reports on the bronchial web in the literature, and the true incidence of these lesions is unknown as many probably go undetected across the lifespan. We here report a case of a congenital bronchial web and provide a review of the literature of all reported bronchial webs. Our patient is a teenage boy who was diagnosed with a congenital bronchial web obstructing the right main-stem bronchus (RMB) and causing right lung hypoplasia and persistent right middle and right lower lobe collapse. The web was treated successfully using endoscopic ablation by argon plasma coagulation and balloon dilatation. Treatment resulted in remarkable relief of right main stem obstruction and significant improvement in right lung collapse as well as clinical, spirometric, and radiological findings. Due to the rarity of bronchial web, the clinical knowledge and the bronchoscopic interventional strategies demonstrated of this report make it relevant. Furthermore, it emphasizes that early diagnosis and management lead to favorable clinical outcomes. Other Information Published in: Respiratory Medicine Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rmcr.2022.101786